Critical Analysis of Road Side Friction on an Urban Arterial Road - Srivastava, Kartik; Kumar, Ajay (Engineering, Technology & Applied Science Research, 2023)
This study reviews the impact of roadside friction on urban arterial roads in the published literature and aims to identify the various side frictional parameters that impact urban arterial roads. The side frictional parameters are non-motorized vehicles, pedestrian crossing or moving along the road, street vendors, on-street parking, animal movement, and land-use activity. The impact of all these parameters on traffic performance leads to a reduction in capacity, speed (instantaneous speed, journey speed, travel speed, time mean speed, and space mean speed), level of service, delay, travel time, and travel cost. This study considered online published studies from 1995 to 2022. The available effective width and the percentage reduction in road capacity are related. Road capacity is reduced by 3.37% when the effective width is reduced by 2.95%, while road capacity is reduced by 26.08% when the effective width is reduced by 21.81%.